1998
DOI: 10.1084/jem.187.6.823
|View full text |Cite
|
Sign up to set email alerts
|

A Mutational Analysis of the Binding of Staphylococcal Enterotoxins B and C3 to the T Cell Receptor β Chain and Major Histocompatibility Complex Class II

Abstract: The three-dimensional structure of the complex between a T cell receptor (TCR) β chain (mouse Vβ8.2Jβ2.1Cβ1) and the superantigen (SAG) staphylococcal enterotoxin C3 (SEC3) has been recently determined to 3.5 Å resolution. To evaluate the actual contribution of individual SAG residues to stabilizing the β–SEC3 complex, as well as to investigate the relationship between the affinity of SAGs for TCR and MHC and their ability to activate T cells, we measured the binding of a set of SEC3 and staphylococcal enterot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
126
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 36 publications
(63 reference statements)
4
126
1
Order By: Relevance
“…Expression of CD70 and CD27 antigens was monitored over a period of 6 days. SAG were used to provide a means of polyclonal T cell activation under conditions mimicking best T cell antigen receptor͞MHC͞peptide affinities in the presence of DC costimulation (23,24). Consistent with previously published data, we found that CD8 ϩ CTL uniformly and rapidly up-regulate CD70 molecules, with peak expression between day 2 and 4 as assessed by three-color flow cytometry analysis ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…Expression of CD70 and CD27 antigens was monitored over a period of 6 days. SAG were used to provide a means of polyclonal T cell activation under conditions mimicking best T cell antigen receptor͞MHC͞peptide affinities in the presence of DC costimulation (23,24). Consistent with previously published data, we found that CD8 ϩ CTL uniformly and rapidly up-regulate CD70 molecules, with peak expression between day 2 and 4 as assessed by three-color flow cytometry analysis ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…Thus, it appears that the high affinity MHC binding site can circumvent the requirement for stabilizing interactions between the TCR and MHC class II (19). Mutagenesis of SEC3 showed a direct correlation between the affinity of SEC3 for the TCR ␤-chain and mitogenicity (5). Recently, phage display was used to engineer SEC3 variants in the disulfide loop with increased affinities to the ␣/␤ TCR revealing that increasing affinity of the SEC3/TCR complex above that normally seen with SAG/TCR interactions resulted in increased T cell activation (8).…”
Section: Discussionmentioning
confidence: 99%
“…Andersen et al (6) have elegantly shown that the TCR ␣-chain interacts with the MHC ␤-chain to stabilize the trimeric complex involving SEB. Although, the TCR/SPE C/MHC class II model predicts that in this interaction SAG acts as a bridge without any direct interactions between TCR and MHC class II, SPE C contains a high affinity (K d ϭ ϳ 4 ϫ 10 Ϫ8 M), zinc-dependent, MHC class II binding domain (19), and small changes in MHC affinity can overcome larger increases in TCR affinity (5). Thus, it appears that the high affinity MHC binding site can circumvent the requirement for stabilizing interactions between the TCR and MHC class II (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this association made perfect biological sense based on the known central role of SAgs in the human disease, mice are not susceptible to SAgs due to an inherent lower affinity of mouse MHC class II molecules to GAS SAgs. The role of GAS SAgs can be well investigated in HLA class II transgenic mice as others and we have reported (Leder et al, 1998;Andersen et al, 1999;Welcher et al, 2002;Nooh et al, 2007). However, due to the overwhelming response to SAgs in these mice, it is difficult to use them to dissect host response to other GAS virulence factors in the disease process.…”
Section: Discussionmentioning
confidence: 99%